A new route to polyoxometalates via mechanochemistry. Issue 4 (12th January 2022) - Wilke, Manuel; Casati, Nicola
Abstract : Under mild conditions, molybdenum POMs could be achieved mechanochemically from simple building blocks, within short reaction times. In situ investigations reveal the formation of intermediates and help explaining the mechanism behind the reaction. Abstract : Mechanochemistry offers a new route to polyoxometalates (POMs) under mild conditions. The molybdenum isoPOM heptamolybdate and the molybdenum heteroPOMs of the Strandberg- and Keggin-type could be achieved from grinding together molybdenum oxide, potassium or ammonium carbonate and phosphate. The reactions were controlled by the stoichiometric ratio of the starting materials and the liquid used, with reaction times between 30 min and 3 h. In situ investigations of the syntheses reveal the formation of intermediates during the reactions. Their identification helps explaining the mechanism of formation of the intermediates as well as the final POMs.